Fellow Eye Macular Edema Improvement after Intravitreal Bevacizumab for Radiation Retinopathy - Isis A. S. Brito; Leandro C. Zacharias; Sérgio Luis G. Pimentel (Case Reports in Ophthalmological Medicine)
Radiation retinopathy (RR) is a progressive, chronic condition directly related to the amount of radiation administered to the retina. We report a 37-year-old patient with medulloblastoma that was treated with external beam radiation and presented to us with bilateral cystoid macular edema. He was treated with monthly bevacizumab injections only in his worst seeing eye. There was a significant improvement in his fellow eye, with marked retinal thickness reduction. Therefore, we present clinical evidence of systemic absorption and fellow eye activity of the drug (bevacizumab). One must be aware of distant side effects after intravitreal injections.